How the Plant Growth-Promoting Bacterium Azospirillum Promotes Plant Growth—A Critical Assessment - Bashan, Yoav; de-Bashan, Luz E. (Advances in Agronomy, 2010)
During the last 35 years of studies of Azospirillum–plant interaction, over 20 proposals were suggested for the mechanism of action by which Azospirillum spp., the most intensively studied plant growth-promoting bacteria, enhances plant growth. The proposals include a single phytohormone activity, multiple phytohormones, nitrogen fixation, assortments of small-sized molecules and enzymes, enhanced membrane activity, proliferation of the root system, enhanced water and mineral uptake, mobilization of minerals, mitigation of environmental stressors of plants, and direct and indirect biological control of numerous phytopathogens. By volume, the largest number of published information involves hormonal activities, nitrogen fixation, and root proliferation. After analyzing the accumulated knowledge, it was concluded that this versatile genus possesses a large array of potential mechanisms by which it can effect plant growth. Consequently, this review proposes the “Multiple Mechanisms Theory,” based on the assumption that there is no single mechanism involved in promotion of plant growth by Azospirillum, but a combination of a few or many mechanisms in each case of inoculation. These may vary according to the plant species, the Azospirillum strain, and environmental conditions when the interaction occurred. The effect can be cumulative, an “additive hypothesis” (proposed before), where the effects of small mechanisms operating at the same time or consecutively create a larger final effect on plant. Additionally, the observed effect on plant growth can be the result of a tandem or a cascade of mechanisms in which one mechanism stimulates another, yielding enhanced plant growth, such as the plausible relations among phytohormones, nitric oxide, membrane activities, and proliferation of roots. Finally, the growth promotion can also be a combination of unrelated mechanisms that operate under environmental or agricultural conditions needed by the crop at particular locations, such as mitigating stress (salt, drought, toxic compounds, adverse environment), and the need for biological control of or reducing pathogenic microflora.